Managing Schools in Brussels: Selection and Local Interdependencies - Perrine Devleeshouwer (LED Edizioni Universitarie, 2015)
This paper underlines selection processes in the Belgian educational school system. It analyses the schools' reactions to the recent modification of the enrolment policy that diminishes the freedom that schools have historically benefitted from to regulate their population. The paper shows that the management variations between schools have to be understood with regard to the local interdependencies between them. These local interdependencies constitute hierarchies that form a frame for individual actions in school which contribute to reproduce the hierarchical structure. Doing so, it insists on the necessity to understand the quasi-market and the competition between schools by taking in account the local social and demographic context. School managing practices are not only due to a mechanical cause-effect link with their position in the educational hierarchies. This paper shows that, when studying the actors' perception in detail, the hierarchies constitute a frame for their actions at a more local level. In this sense, the weight of hierarchies and interdependencies is not automatically built on the spaces defined by flow of pupils between schools. Theses spaces are not a fixed frame for educational actions even within schools sharing a similar position in the hierarchies.